Elevated virus infection of honey bee queens reduces methyl oleate production and destabilizes colony-level social structure - Alison McAfee; Abigail Chapman; Armando Alcazar Magaña; Katie E. Marshall; Shelley E. Hoover; David R. Tarpy; Leonard J. Foster (Proceedings of the National Academy of Sciences, 2025)
Pathogenic threats to reproductive individuals pose a profound challenge to the stability of insect societies. In honey bees ( Apis mellifera L.), severe virus infections in queens can trigger worker-initiated supersedure, a socially coordinated replacement of the queen that, while risky, is essential when her reproductive competence is compromised. How viruses impact the physiology of queen hosts, who bear unique reproductive burdens within their colonies, and how this perturbs colony social order remains poorly understood. We hypothesized that the supersedure response is mediated by pathogen-induced, intensity-dependent changes in queen pheromonal signaling. Laboratory infection experiments revealed that queens challenged with deformed wing virus B and black queen cell virus infections demonstrated a reduction in methyl oleate, a key component of the queen retinue pheromone, and field data corroborated this association. Lipidomics analysis demonstrated that infection coincides with a systemic lipid deficiency, especially in triacylglycerides (major energy reserves), providing a physiological link among viral stress, ovarian atrophy, and altered pheromone output. Notably, artificial suppression of ovary investment via restricted laying also caused methyl oleate production to decline; therefore, high virus infection likely indirectly suppresses methyl oleate production by reducing ovary mass. In field trials, we further show that synthetic pheromone blends containing methyl oleate significantly suppressed queen cell rearing compared to no-pheromone controls, whereas blends lacking this compound yielded an intermediate effect. These results demonstrate that virus-induced reproductive decline disrupts pheromone signaling, revealing a plausible mechanistic pathway by which pathogens can erode social cohesion.